Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1080/17470218.2012.754909
|View full text |Cite
|
Sign up to set email alerts
|

A look into the ballot box: Gaze following conveys information about implicit attitudes toward politicians

Abstract: Although considered a predominantly automatic social behaviour, gaze following (GF) is sensitive to complex social factors like political affiliation and ideology. The present study aimed to determine whether the differential proneness to in-group leaders' gaze is related to attitudes towards politicians as measured by other implicit procedures. A GF paradigm was used to test the extent to which electors were prone to gaze following when attending to two female candidates who competed for the position of gover… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
22
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 20 publications
(39 reference statements)
4
22
0
Order By: Relevance
“…gaze-following and gaze cueing22). Previous studies indicate that observing directionally oriented saccades automatically triggers in an onlooker the tendency to make a saccade directed in the same direction232431 and activates fronto-parietal and temporal cortical regions similar to those recruited during actual execution of eye movements3233. Here, we found that seeing one's own saccades triggered an oculomotor program that maximally interfered with the ongoing programming and execution of saccades directed in the opposite direction.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…gaze-following and gaze cueing22). Previous studies indicate that observing directionally oriented saccades automatically triggers in an onlooker the tendency to make a saccade directed in the same direction232431 and activates fronto-parietal and temporal cortical regions similar to those recruited during actual execution of eye movements3233. Here, we found that seeing one's own saccades triggered an oculomotor program that maximally interfered with the ongoing programming and execution of saccades directed in the opposite direction.…”
Section: Discussionsupporting
confidence: 54%
“…Thus, we combined the enfacement paradigm15 with a gaze-following task202324 to explore if experiencing self-other merging with a close other may reduce the distracting power of one's own gaze22 compared to the friend's gaze, and if social perception variables and individual empathic personality traits may drive the power of this effect, as initially found for the enfacement15.…”
mentioning
confidence: 99%
“…For instance, it has recently been shown that when faces of real politicians are used as cue, conservatives and liberals are less influenced by gaze direction of their respective outgroup leaders (Liuzza et al 2011(Liuzza et al , 2013. These results strongly emphasize the importance of political variables in shaping social attention.…”
Section: Discussionmentioning
confidence: 55%
“…A full understanding of joint attention requires us to understand these top-down processes. For example, we are more likely to follow the gaze of certain individuals such as people who are of high status (Dalmaso, Pavan, Castelli, & Galfano, 2012), or of our own political persuasion (Liuzza et al, 2013) or race (Dalmaso, Galfano, & Castelli, 2015). Whilst several papers have reported gaze following to be independent of emotional expression (Bayliss, Frischen, Fenske, & Tipper, 2007;Hietanen & Leppanen, 2003;Holmes, Richards, & Green, 2006), it has become apparent that when participants were required to detect an emotionally salient target, the emotional expression does influence gaze cueing, with stronger cueing for fearful than for happy faces (Bayliss, Schuch, & Tipper, 2010;Kuhn & Tipples, 2011;Pecchinenda, Pes, Ferlazzo, & Zoccolotti, 2008), which suggests that joint attentional processes may be more strategic than previously thought (Baron-Cohen, 1995).…”
Section: Own-age Biases In Adults' and Children's Joint Attention: Bimentioning
confidence: 99%